Rotating magnetoconvection with ohmic heating ... / [mikrofilem] - 498071 Maslan Osman; Mohamad Hassan Zakaria; Mohammad Nazri Mohd. Ja'afar; Rosli Md. Illias; Rosly Abdul Rahman (Skudai : Universiti Teknologi Malaysia, 1997)
Thesis (Doctor of Philosophy) - University of Newcastle upon Tyne, 1997